TEACHERS LANGUAGE ASSESSMENT LITERACY: A SYSTEMATIC REVIEW - Indah Puspawati (Universitas Kuningan, 2022)
As an integral part of teaching, assessment is critical since the information from the assessment is essential for many decisions in teaching and learning. Therefore, teachers must hold sufficient knowledge of assessment literacy. The interest in developing Language Assessment Literacy (LAL) has grown rapidly in the last few years. This growing interest for teachers LAL has sparked discussions related to the topics. This article aims to review research conducted related to the topic of teachersâ LAL. This research used a systematic review as the research methodology where 21 articles from various peer-reviewed and reputable journals related to language assessment literacy in the past five years were reviewed to understand LAL comprehensively. Five steps of the systematic review were done in this research, namely framing the questions, identifying relevant works, assessing the quality of the studies, summarizing the evidence, and interpreting the findings. The findings of the reviews reported that the research of LAL in the past five years were teachersâ LAL beliefs, the LAL beliefs and their assessment practices, teachersâ LAL training needs, and developing teachersâ LAL. The findings also suggested that teachers were still in needs of continuous support to develop teachersâ LAL because they lack of LAL training both for pre-service and in-service training. This research recommended that LAL training should be carefully planned to cater the needs of teachers assessment practices. Keywords: Language Assessment Literacy; teachersâ language assessment literacy; LAL beliefs, assessment practices, systematic review